Respuesta :
The answer is a. x=10, y=-36
We have two equations.
Let's rearrange one of them:
6x + y = 24
y = 24 - 6x
Now, write those two equations together:
y = 24 - 6x
3x + y/3 = 18
Substitute y in the second equation and solve it for x:
3x + (24 - 6x)/3 = 18
3x + 24/3 - 6x/3 = 18
3x + 8 - 2x = 18
3x - 2x = 18 - 8
x = 10
Now, using the first equation calculate y:
y = 24 - 6x
y = 24 - 6 * 10
y = 24 - 60
y = -36
We have two equations.
Let's rearrange one of them:
6x + y = 24
y = 24 - 6x
Now, write those two equations together:
y = 24 - 6x
3x + y/3 = 18
Substitute y in the second equation and solve it for x:
3x + (24 - 6x)/3 = 18
3x + 24/3 - 6x/3 = 18
3x + 8 - 2x = 18
3x - 2x = 18 - 8
x = 10
Now, using the first equation calculate y:
y = 24 - 6x
y = 24 - 6 * 10
y = 24 - 60
y = -36